O polskich i słowackich depeszach kondolencyjnych w związku z atakami terrorystycznymi - Olchowa, Gabriela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
Occasional magazines were discussed, specifically condolences in the Polish-Slovak comparative approach. We analyzed 44 (22 PL / 22 SK) condolences delivered in the years 2015–2017 by the President of the Republic Andrzej Duda and the President of the Slovak Republic Andrej Kiska in connection with terrorist attacks. The characteristic features of condolence messages sent after terrorist attacks were indicated. Based on the collected material, two compositional diagrams and their obligatory components were distinguished. Many similarities have been found in Polish and Slovak condolence messages, which mainly originates from the diplomatic style, which imposes some formal requirements, but also some differences were noticed.